Environmental benefit assessment of steel slag utilization and carbonation: A systematic review - Li, Lufan; Ling, Tung-Chai; Pan, Shu-Yuan (The Science of the total environment, 2022)
The rapid increase in steel slag generation globally highlights the urgent need to manage the disposal or utilization processes. In addition to conventional landfill disposal, researchers have successfully reused steel slag in the construction, chemical, and agricultural fields. With the large portions of alkaline silicate mineral content, steel slag can also be used as a suitable material for carbon capture to mitigate global warming. This article comprehensively reviews the environmental performance of steel slag utilization, especially emphasizing quantitative evaluation using life cycle assessment. This paper first illustrates the production processes, properties, and applications of steel slag, and then summarizes the key findings of the environmental benefits for steel slag utilization using life cycle assessment from the reviewed literature. This paper also identifies the limitations of quantifying the environmental benefits using life cycle assessment. The results indicate steel slag is largely utilized in pavement concrete and/or block as a substitution for natural aggregates. The associated environmental benefits are mostly attributed to the avoidance of the large amount of cement utilized. The environmental benefits for the substitution of traditional energy-intensive material and carbonation treatment are further discussed in detail. Due to the presence of heavy metals, the potential risks to human and ecological health caused by the manufacturing process and usage stage are examined. Finally, the current challenges and global social implications for steel slag valorization are summarized. [Display omitted] •System expansion and allocation choices may lead to opposite interpretations.•Environmental benefit caused by replacement of steel slag aggregate is limited.•Mitigation of climate change is easy to be achieved by reducing cement addition.•Carbonation method should be optimized to maximize the carbon capture benefit.